Dynamic optimization of thermodynamically rigorous models of multiphase flow in porous subsurface oil reservoirs. (June 2019) - Ritschel, Tobias K.S.; Jørgensen, John Bagterp
Highlights: We present novel thermal and isothermal compositional reservoir flow models. We use the UV and the VT flash to describe the phase equilibrium in these models. We formulate the UV and the VT flash as optimization problems. We use a gradient-based algorithm for dynamic optimization of the two flow models. We compare the computational performance of the algorithm for the two flow models. Abstract: In this paper, we consider dynamic optimization of thermal and isothermal oil recovery processes which involve multicomponent three-phase flow in porous media. We present thermodynamically rigorous models of these processes based on 1) conservation of mass and energy, and 2) phase equilibrium. The conservation equations are partial differential equations. The phase equilibrium problems that are relevant to thermal and isothermal models are called the UV and the VT flash, and they are based on the second law of thermodynamics. We formulate these phase equilibrium problems as optimization problems and the phase equilibrium conditions as the corresponding first order optimality conditions. We demonstrate that the thermal and isothermal flow models are in a semi-explicit differential-algebraic form, and we solve the dynamic optimization problems with a previously developed gradient-based algorithm implemented in C/C++. We present numerical examples of optimized thermal and isothermal oil recovery strategies and discuss the computational performance of the dynamic optimization algorithm in these examples.